Does Geography Shape the Nature of an Educational Innovation? - Jo Luck (Journal of Research in Rural Education, 2003)
This article examines some of the social, technical, and economic issues encountered in the implementation of an educational technology at an Australian regional university. Reference is made to the implementation of the videoconferencing network at Central Queensland University (CQU). In late 1996 when the implementation process was completed the videoconferencing network was unique in universities within Australia. The article, which is based on current doctoral research, explores the reasons for the development of this videoconferencing network and its effect on academic teaching in the videoconferencing environment. The implications of this study for understanding geographical influence on educational innovations are also considered. The geographical isolation of the campuses at CQU helped to shape a unique teaching model using the interactive videoconferencing network.